2021
DOI: 10.1111/ajgw.12499
|View full text |Cite
|
Sign up to set email alerts
|

Regionality in Australian Shiraz: compositional and climate measures that relate to key sensory attributes

Abstract: Background and Aims Regional characters or the ‘terroir’ aspects of Shiraz are not well understood. This study aimed to characterise the chemical composition of wines from sites within six important Australian regions, and the climate profiles of the sites, and to determine how they relate to sensory differences. Methods and Results For 22 commercially produced wines 70 chemical measures and 17 site‐ and season‐specific climate indices were determined. Wines with stalky/cooked vegetal sensory properties had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Recent research has demonstrated that Australian Shiraz wines from distinct geographical regions can be reliably distinguished on the basis of both their sensory characteristics (Pearson et al 2020) and the chemical composition of their volatile constituents (Li et al 2021) with these attributes collectively related to differences in regional climate (Pearson et al 2021). Kustos et al (2020) have noted, however, that even though a regional typicality might be discernible using such techniques, consumers may not perceive these differences in tasting.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that Australian Shiraz wines from distinct geographical regions can be reliably distinguished on the basis of both their sensory characteristics (Pearson et al 2020) and the chemical composition of their volatile constituents (Li et al 2021) with these attributes collectively related to differences in regional climate (Pearson et al 2021). Kustos et al (2020) have noted, however, that even though a regional typicality might be discernible using such techniques, consumers may not perceive these differences in tasting.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been applied for instance to wine classification using ICP MS 15 , nuclear magnetic resonance 16 , RP-HPLC/DAD 5 and UV-spectroscopy 17 or to wine region classification using GC/QTOFMS 18 , isotopic ratio 19 , absorbance-transmission and fluorescence excitation-emission matrix (A-TEEM) or climate data 20 . Other studies have also looked at sensorial properties and aroma profiles using gas chromatography (GC) 21 and wine quality using global chemical measurements (alcoholic contents or acidity as examples) 22 and the emergence of oxidative markers during aging with GC 23 .…”
mentioning
confidence: 99%
“…We construct two mean weather variables: growing season average temperature (GST), defined as GST=1kd=1d=k[]()minimum temperature+maximum temperature/2, where d=1 is the first day of the growing season and d=k is the last day of the growing season; and total growing season precipitation (GSP). While the length of the growing season varies between cultivars and regions in Australia (Pearson et al 2021), and also between years (Jarvis et al 2019, Cameron et al 2021), we define growing season as the period between October and April.…”
Section: Methodsmentioning
confidence: 99%